Greenways for recreation and maintenance of landscape quality: five case studies in Portugal - Ribeiro, Luís Paulo (2018)
The use of the concept of greenway can be identified in Portugal throughout the 20th century as a planning and design tool. Several examples, such as the ‘Improvement Plans for Lisbon’ by Ressano Garcia (1901), the continuum naturale concept [Cabral, F.C., 1980. O Continuum Naturale e a Conservac¸ ˜ao da Natureza. Conservac¸ ˜ao da Natureza. Servic¸o de Estudos do Ambiente, Lisbon; Andresen, T., 2001. Francisco Caldeira Cabral. Landscape Design Trust, Surrey, UK, 213 pp.], the Green Plan for Lisbon [Telles, G.R., et al., 1997. Plano Verde de Lisboa. Ed. Colibri, Lisboa, 197 pp.], deal with the subjects of implementing vegetation corridors, pedestrian networks and landscape quality. These examples establish Portuguese planning and design tradition within the international greenway movement first identified by Fabos [Fabos, J.Gy., 1991. From Park to Greenways into the 21st Century. In: Proceedings from Selected Educational Sessions, ASLA Annual Meeting, Kansas City, Missouri]. Though several projects have been developed at the planning level, there is a need to analyze the applicability of such a concept at the regional, municipal and local level. We must consider the characteristics of Portugal’s cultural landscape, recognition by other professions dealing with planning and involvement by politicians. By analyzing five case studies, this paper shows the significance of the greenway as a planning and design strategy, which coincides, with the current objectives of political and planning authorities at the municipal level. It also proves that it is possible to reconcile political objectives and urban development while safeguarding landscape quality and providing new opportunities for public recreation and education. Greenway planning and design is now undoubtedly a subject of growing significance in Portugal